The Conflict of Jurisdiction between Military and Civil Judiciary - الراشدي وليد بدر نجم (PROSPECTIVE RESEARCHES, 2024)
The current research aims to clarify the position of the Iraqi military legislator on the conflict of jurisdiction after the issuance of the new Military Criminal Procedure Code No. (22) of 2016 and to clarify the concept of jurisdiction in all its linguistic, terminological and legal dimensions and to add a procedural building block that the criminal legislator abandoned or did not address explicitly. The importance of the research is the importance of the subject of jurisdiction, which occupies an important position and is the basis for determining the task of the judiciary, which is entrusted with the task of verifying or denying the accusation of the accused. The researcher reached many conclusions, the most important of which is that jurisdiction refers to the court’s ability to hear the case, while conflict of jurisdiction refers to it. A dispute between two judicial bodies regarding their jurisdiction to hear a particular case. The dispute over jurisdiction may occur between two military courts, or it may occur between a military court and an ordinary criminal court. The researcher recommended the need for the Iraqi legislator to include an explicit and clear text specifying the competent authority in resolving the dispute over positive or negative jurisdiction that occurs between the military courts and the regular criminal courts, in addition to the necessity of giving the parties The lawsuit has the right to request the appointment of the authority responsible for resolving the dispute, and this should not be limited to the court only.